Peran Jaga Warga Dalam Menyelesaikan Konflik Sosial Melalui Collaborative Governance di Lumbungrejo - Aisyah Putri Wulansari; Sri Widayanti (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The research titled "The Role of Community Watch in Resolving Social Conflicts Through Collaborative Governance" aims to understand the manifestation of collaborative governance to examine the correlation relationship between the Village Head, Jagabaya, Babinkamtibmas, Babinsa, Omah Jaga Warga Management, Jaga Warga Management, and the community in synergizing to resolve issues and provide social assistance in the Lumbungrejo Village area. This study employs a qualitative research type with a descriptive method. The research location is in Lumbungrejo Village, with data collection techniques including observation, interviews, and documentation. The number of informants in this study is seven people. In the process of social assistance through Jaga Warga, various parties are involved to help resolve issues. The manifestation of collaborative governance in social assistance through Jaga Warga in the Lumbungrejo area, based on data findings, fulfills all aspects, including active participation, transparency, coordination, trust, benefit-sharing, policies and procedures, as well as technology and information. This study concludes that when experiencing a conflict and needing assistance, the community usually reports it to a Jaga Warga member, who then follows up by the Jaga Warga management. As a facilitator, Jaga Warga will bring together the conflicting parties for deliberation and seek a fair agreement. The solutions provided by Jaga Warga are, of course, the best solutions. However, it is unfortunate that there is no written SOP regarding the implementation of Jaga Warga. Therefore, it is advisable that Jaga Warga in Lumbungrejo has an SOP or standard operating procedure that is socialized to the community and written down so that the community knows what to do first when facing problems they cannot solve on their own.